Physics, asked by aim84631, 6 months ago

deferentation of y=tan√sin√x​

Answers

Answered by kartikkala10december
2

Answer:

Answer is in the attachment.

Hope it helps!!!!

Attachments:
Answered by Anonymous
16

Solution :

:\implies \sf{\dfrac{dy}{dx} = \dfrac{d\left[tan\left(\sqrt {sin(\sqrt{x})}\right)\right]}{d[\sqrt{sin\sqrt{x})}}} \\ \\

\textsf{By using the chain rule of differentiation, we get :} \\ \\ \underline{\sf{\bigstar\:Chain\:rule\:of\: differentiation\: :-}} \\ \\ :\implies \sf{\dfrac{dy}{dx} = \dfrac{dy}{du}\cdot\dfrac{du}{dx}} \\ \\

\sf{Here,}

  • \sf{y = tan\left(\sqrt{sin(\sqrt{x})}\right)} \\ \\
  • \sf{u = \sqrt{sin(\sqrt{x}})} \\ \\

:\implies \sf{\dfrac{dy}{dx} = \dfrac{d\left[tan\left(\sqrt {sin(\sqrt{x})}\right)\right]}{d\left[\sqrt{sin(\sqrt{x})}\right]}\cdot\dfrac{d\left[\sqrt{sin(\sqrt{x})}\right]}{dx}} \\ \\

:\implies \sf{\dfrac{dy}{dx} = sec^{2}\left[\sqrt{sin(\sqrt{x}})\right]\cdot\dfrac{d\left[\sqrt{sin(\sqrt{x})}\right]}{dx}} \\ \\

\textsf{By using the chain rule of differentiation, we get :} \\ \\ \underline{\sf{\bigstar\:Chain\:rule\:of\: differentiation\: :-}} \\ \\ :\implies \sf{\dfrac{dy}{dx} = \dfrac{dy}{du}\cdot\dfrac{du}{dx}} \\ \\

\sf{Here,}

  1. \sf{y = \sqrt{sin(\sqrt{x})}} \\ \\
  • \sf{u = sin(\sqrt{x})} \\ \\

:\implies \sf{\dfrac{dy}{dx} = sec^{2}\left[\sqrt{sin(\sqrt{x}})\right]\cdot\dfrac{d\left[\sqrt{sin(\sqrt{x})}\right]}{d\left[sin(\sqrt{x})\right]}\cdot\dfrac{d\left[sin(\sqrt{x})\right]}{dx}} \\ \\

:\implies \sf{\dfrac{dy}{dx} = sec^{2}\left[\sqrt{sin(\sqrt{x}})\right]\cdot \dfrac{1}{2}sin(\sqrt{x})^{\left(\tiny{\dfrac{1}{2} - 1}\right)}\cdot\dfrac{d\left[sin(\sqrt{x})\right]}{dx}} \\ \\

:\implies \sf{\dfrac{dy}{dx} = sec^{2}\left[\sqrt{sin(\sqrt{x}})\right]\cdot \dfrac{1}{2}sin(\sqrt{x})^{-\tiny{\dfrac{1}{2}}}\cdot\dfrac{d\left[sin(\sqrt{x})\right]}{dx}} \\ \\

:\implies \sf{\dfrac{dy}{dx} = sec^{2}\left[\sqrt{sin(\sqrt{x}})\right]\cdot \dfrac{1}{2\sqrt{sin(\sqrt{x})}}\cdot\dfrac{d\left[sin(\sqrt{x})\right]}{dx}} \\ \\

\textsf{By using the chain rule of differentiation, we get :} \\ \\ \underline{\sf{\bigstar\:Chain\:rule\:of\: differentiation\: :-}} \\ \\ :\implies \sf{\dfrac{dy}{dx} = \dfrac{dy}{du}\cdot\dfrac{du}{dx}} \\ \\

\sf{Here,}

  • \sf{y = sin(\sqrt{x})} \\ \\
  • \sf{u = \sqrt{x}} \\ \\

:\implies \sf{\dfrac{dy}{dx} = sec^{2}\left[\sqrt{sin(\sqrt{x}})\right]\cdot \dfrac{1}{2\sqrt{sin(\sqrt{x})}}\cdot\dfrac{d\left[sin(\sqrt{x})\right]}{d(\sqrt{x})}\cdot \dfrac{d(\sqrt{x})}{dx}} \\ \\

:\implies \sf{\dfrac{dy}{dx} = sec^{2}\left[\sqrt{sin(\sqrt{x}})\right]\cdot \dfrac{1}{2\sqrt{sin(\sqrt{x})}}\cdot cos(\sqrt{x})\cdot \dfrac{1}{2}x^{\left(\tiny{\dfrac{1}{2} - 1}\right)}} \\ \\

:\implies \sf{\dfrac{dy}{dx} = sec^{2}\left[\sqrt{sin(\sqrt{x}})\right]\cdot \dfrac{1}{2\sqrt{sin(\sqrt{x})}}\cdot cos(\sqrt{x})\cdot \dfrac{1}{2}x^{-\tiny{\dfrac{1}{2}}}} \\ \\

:\implies \sf{\dfrac{dy}{dx} = sec^{2}\left[\sqrt{sin(\sqrt{x}})\right]\cdot \dfrac{1}{2\sqrt{sin(\sqrt{x})}}\cdot cos(\sqrt{x})\cdot \dfrac{1}{2\sqrt{x}}} \\ \\

:\implies \sf{\dfrac{dy}{dx} = \dfrac{sec^{2}\left[\sqrt{sin(\sqrt{x}})\right]cos(\sqrt{x})}{4\sqrt{sin(\sqrt{x})}\sqrt{x}}} \\ \\

\boxed{\underline{\therefore \sf{\dfrac{dy}{dx} = \dfrac{sec^{2}\left[\sqrt{sin(\sqrt{x}})\right]cos(\sqrt{x})}{4\sqrt{sin(\sqrt{x})}\sqrt{x}}}}}

Similar questions